Management of risk through seepage reduction for two earth dams in Kurdistan region, Iraq - Abdulkareem, Sangar Hasan; Ahmed, Thamer Mohamed; Ghazali, Abdul Halim (Asian Research Publishing Network, 2014)
Risk management through seepage reduction for earth fill dams with evaluation of risk and reliability has been a major concern for the hydrosystem and geotechnical engineers. Several techniques have been established to measure risk and reliability of a system. One of the main approach of risk reduction for seepage at earthen dams is modeling technique. In case of existence of seepage problem through or underneath the earth dams, reliability of the analysis should be based on review of as-built drawing and construction/operation photography of the dam site in order to tackle the defects which cause the problem. This study aimed at managing the seepage risk reduction of two existing zoned earthen dams that newly constructed in Kurdistan Region, Iraq, namely Hamamuk dam and Bawashaswar dam. Both dams have been suffering from downstream flat slope seepage since initial filling. For this purpose, construction/operation photography were reviewed and SEEP/W models wasplied. Construction defects that caused seepage problems at both dams were detected based on the construction/operation photography. Also, the effects of these defects on seepage rate and seepage path were simulated using SEEP/W model. Appropriate solutions were proposed based on different guidelines and references.